2004
DOI: 10.1007/s10038-004-0143-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel susceptibility locus for moyamoya disease on chromosome 8q23

Abstract: Moyamoya disease (MIM 252350) is characterized by stenosis or occlusion of the terminal portions of the bilateral internal carotid arteries and by abnormal vascular networks at the base of the brain. There is a high incidence of moyamoya disease in Asia, especially in Japan. Multifactorial inheritance is estimated with ks>40. Previous linkage studies have indicated that susceptibility loci for the disease are located on chromosomes 3p, 6q, and 17q. In the present study, we searched for loci linked to the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(89 citation statements)
references
References 11 publications
1
86
0
2
Order By: Relevance
“…The etiology of moyamoya disease remains unknown, while recent findings suggest the importance of genetic factors (Ikeda et al 1999;Inoue et al 2000;Yamauchi et al 2000;Sakurai et al 2004). A more recent genome-wide association study identified the ring finger protein (RNF) 213 gene (RNF213) in the 17q25-ter region as a susceptibility gene for moyamoya disease among East Asian population (Kamada et al 2011), although the exact function of RNF213 is undetermined.…”
Section: Genetics: Significance Of Rnf213 Susceptibility Genementioning
confidence: 99%
“…The etiology of moyamoya disease remains unknown, while recent findings suggest the importance of genetic factors (Ikeda et al 1999;Inoue et al 2000;Yamauchi et al 2000;Sakurai et al 2004). A more recent genome-wide association study identified the ring finger protein (RNF) 213 gene (RNF213) in the 17q25-ter region as a susceptibility gene for moyamoya disease among East Asian population (Kamada et al 2011), although the exact function of RNF213 is undetermined.…”
Section: Genetics: Significance Of Rnf213 Susceptibility Genementioning
confidence: 99%
“…As shown in Table 4, four reports from Japan have conducted linkage analysis by using microsatellite markers to specify the susceptible genetic loci on familial moyamoya disease. 22,25,54,77) These reports have specified the susceptible linkage at 3p24.2-p26, 6q25, 17q25, and 8q23 for familial moyamoya disease. A suggestive linkage at 12p12 has also been demonstrated.…”
Section: Geneticsmentioning
confidence: 99%
“…9 Second, the concordance rate of MMD in monozygotic twins is as high as 80%. 10 Third, the prevalence of MMD is 10 times higher in East Asia, especially in Japan (6 per 100 000 population), than in Western countries. 3 Familial MMD may be inherited in an autosomal dominant fashion with low penetrance or in a polygenic manner.…”
Section: Introductionmentioning
confidence: 97%